A tangle of gold - Moriarty, Jaclyn (Moriarty, Jaclyn. Colors of Madeleine, 2016)
In Cambridge, England, Madeleine Tully is still working to gather the Royal Family, and get them back to their parallel world--but in Cello, Elliot Baranski is being held captive, the Hostiles are working against the Royal Family, and the World Severance Unit is trying to stop all contact between Cello and the World for good.